The Experiments of Radeef in Ghazliat of Wali Dakni - Muhammad Naveed Abbas Shahid; Akbar, Dr. Sumaira (Zaban-o-Adab, 2023)
This article elaborates the Use of Radeef in Ghazaliat of Wali Dakhni. Wali Dakhni is considered as the father of the Urdu poetry. Before the advent of his Divan Urdu Poetry was surrounded by the words from other languages. He unraveled the beauty and richness of the Urdu language as a poetic medium. He expressed both mystical and earthly love in his Radeef adeptly. His radeef contain all the aesthetic, artistic and dianoetic aspects of Urdu poetry. He used exclamatory, singular, narrative, interrogative, imperative, temporal, optative and multiple and varied meanings words as Radeef.